Likelihood calculations for reconstructed lacunae and Papyrus 46's text of Ephesians 6:19. - McCollum, Joey (Digital Scholarship in the Humanities, 2023)
This article presents an approach to quantify the likelihood of a given reconstruction of lacunose text in a manuscript using statistics on line lengths (in letters), information about the line-breaking conventions and scribal habits of the scribe who copied the manuscript, and the well-known computational technique of dynamic programming. The approach and its value are illustrated with an application to a textual contest between the readings τὸ μυστήριον τοῦ εὐαγγελίου and τὸ μυστήριον in Ephesians 6:19, where the early papyrus witness P. Chester Beatty II/P. Mich. Inv. 6238 (Gregory–Aland P ) is lacunose. The study shows that under reasonable assumptions, P is over fifty times more likely to have read τὸ μυστήριον.